2016
DOI: 10.1016/j.jnc.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Habitats on the grid: The spatial dimension does matter for red-listing

Abstract: a b s t r a c tBesides species Red Lists, recently, a variety of frameworks have been proposed for assessing higher levels of biological organisation, i.e. ecosystems, habitats, plant communities. Most of these protocols refer to 'plant species assemblages' or 'vegetation types' as proxies for ecosystems or habitats. Indeed, the habitat concept based on plant communities has acquired a central role as a key approach for biodiversity conservation above the species level. Plant communities, like every complex bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Importantly, our analyses suggested that forest moss cover reported in the literature for temperate broadleaf forests tends to overestimate moss cover compared with the estimates obtained by systematic surveys, suggesting a potential bias towards higher moss cover values in studies focused on moss communities of temperate broadleaf forests—possibly attributable to selection of moss‐rich sites or microsites in areas where moss cover is variable but generally less abundant (Cavard et al, ). Then, the spatial heterogeneity of the moss layer might be higher compared with that of its hosting forest, as expected from the variability of spatial heterogeneity across scales (Gigante, Foggi, Venanzoni, Viciani, & Buffa, ; Palmer, ). Notably, the bias of published studies towards higher moss abundance was not present in the boreal coniferous forests, where moss was much more abundant than in the temperate broadleaf forests (cf.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, our analyses suggested that forest moss cover reported in the literature for temperate broadleaf forests tends to overestimate moss cover compared with the estimates obtained by systematic surveys, suggesting a potential bias towards higher moss cover values in studies focused on moss communities of temperate broadleaf forests—possibly attributable to selection of moss‐rich sites or microsites in areas where moss cover is variable but generally less abundant (Cavard et al, ). Then, the spatial heterogeneity of the moss layer might be higher compared with that of its hosting forest, as expected from the variability of spatial heterogeneity across scales (Gigante, Foggi, Venanzoni, Viciani, & Buffa, ; Palmer, ). Notably, the bias of published studies towards higher moss abundance was not present in the boreal coniferous forests, where moss was much more abundant than in the temperate broadleaf forests (cf.…”
Section: Discussionmentioning
confidence: 93%
“…Habitats, in the pragmatic definition given in European Directives (Commission of the European Community, 1992;European Commission, 2013;Evans, 2006Evans, , 2010, are considered to be a cornerstone of European nature conservation policy, because the maintenance of a series of habitats in good condition is one of the best ways to conserve species and biodiversity (Berg et al, 2014;Bunce et al, 2013;Evans, 2012;Gigante, Foggi, Venanzoni, Viciani, & Buffa, 2016;Kontula & Raunio, 2009;Nicholson, Keith, & Wilcove, 2009;Rodríguez et al, 2011Rodríguez et al, , 2012Rodríguez et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…; Gigante et al. ). Gaston and Fuller () note “significant confusion in the literature over the measurement and interpretation of geographic ranges, and … that [spatial metrics used in red listing] should not be regarded as more or less accurate ways of measuring range size.” The evidence from our risk analyses should help resolve confusion between the application of AOO on one hand as a measure of occupied habitat in biogeographic analysis and on the other hand as an indicator of risk in red‐list assessments.…”
Section: Discussionmentioning
confidence: 98%
“…(), and Gigante et al. (). Authors of each of these studies claim that AOO measured at recommended scales under‐ or overestimate risks, but none attempt to quantify risks or explore how the spatial features of threats influence risks through their interactions with those of biological distributions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation